Prospects for Forming an Alternative Financial System - Burkhanov Aktam Usmanovich; Nizomiddinov Jahonmirzo Zukhriddin o’g’li (Research Parks Publishers, 2023)
Legal and financial relations in the conditions of a free market economy new by individuals voluntarily pooling their resources to the establishment of business entities and previously established ones leads to the expansion of the scope of activity through the financial market. Exactly in the financial market, which is distributed to various sectors of the national economy the main part of the income is formed, and these incomes are of economic development and serves as the main source of social development.